PI3K and Inhibitor of Apoptosis Proteins Modulate Gentamicin- Induced Hair Cell Death in the Zebrafish Lateral Line - Wiedenhoft, Heather; Hayashi, Lauren; Coffin, Allison B. (Frontiers in Cellular Neuroscience, 2017)
Inner ear hair cell death leads to sensorineural hearing loss and can be a direct consequence of aminoglycoside antibiotic treatment. Aminoglycosides such as gentamicin are effective therapy for serious gram-negative bacterial infections such as some forms of meningitis, pneumonia, and sepsis. Aminoglycosides enter hair cells through mechanotransduction channels at the apical end of hair bundles and initiate intrinsic cell death cascades, but the precise cell signaling that leads to hair cell death is incompletely understood. Here, we examine the cell death pathways involved in aminoglycoside damage using the zebrafish (Danio rerio). The zebrafish lateral line contains hair cell-bearing organs called neuromasts that are homologous to hair cells of the mammalian inner ear and represents an excellent model to study ototoxicity. Based on previous research demonstrating a role for p53, Bcl2 signaling, autophagy, and proteasomal degradation in aminoglycoside-damaged hair cells, we used the Cytoscape GeneMANIA Database to identify additional proteins that might play a role in neomycin or gentamicin ototoxicity. Our bioinformatics analysis identified the pro-survival proteins phosphoinositide-dependent kinase-1 (PDK1) and X-linked inhibitor of apoptosis protein (Xiap) as potential mediators of gentamicin-induced hair cell damage. Pharmacological inhibition of PDK1 or its downstream mediator protein kinase C facilitated gentamicin toxicity, as did Xiap mutation, suggesting that both PI3K and endogenous Xiap confer protection. Surprisingly, aminoglycoside-induced hair cell death was highly attenuated in wildtype TL fish (the background strain for the Xiap mutant line) compared to wildtype *AB zebrafish. Pharmacologic manipulation of p53 suggested that the strain difference might result from decreased p53 in TL hair cells, allowing for increased hair cell survival. Overall, our studies identified additional steps in the cell death cascade triggered by aminoglycoside damage, suggesting possible drug targets to combat hearing loss resulting from aminoglycoside exposure.